'Action Not Words': The Conservative Party, Public Opinion and 'Scientific' Politics, c.1945–70. (24th June 2019) - Lockwood, Charles
Abstract: From the late 1950s, Conservative research and policy thinkers underwent a conscious intellectual adjustment, which had profound implications for how the party conceived the relationship between politicians and the public during Edward Heath's period as Conservative leader after 1965. In response to contemporaneous debates regarding 'modernization', and as a result of their engagement with the emergent social sciences, a new generation of Conservatives tended to repudiate the party's traditional preference for idealist and organicist philosophical assumptions in favour of a rationalistic approach to political administration. Their preoccupation with economic management was concomitant of their loss of faith in the formative role of rhetorical and moral appeals in shaping public opinion. This article, by focusing on debates within the party's research and political apparatus—the Conservative Research Department, the Conservative Political Centre and Swinton College—will contend that, far from being the last gasp of a post-war consensual Conservatism, Heath's period as leader marked a relatively unique period in the party's history, in which the conception of the nature of political leadership held by those at the top of the party differed from the conception held by both their predecessors and successors.